Hubungan Beban Kerja Dengan Tingkat Stres Kerja Perawat IGD Di RS X Provinsi Jawa Barat Tahun 2025 - Lukman, Ardeliea Fitriyanti; Tohri, Tonika; Manumara, Theophylia Melisa; Rustandi, Budi (Journal of Innovative and Creativity, 2026)
Background: Emergency Room nurses generally have excessive workloads physically, in terms of skills and available time, which affects a person's emotions, thought processes, and conditions, causing work stress. Workload is a condition when there is an imbalance between a worker's abilities or capabilities and the demands of the work that must be completed. Objective: This study aims to determine the relationship between workload and the level of work stress of nurses in the Emergency Room of Hospital X. Method: The research design used is quantitative with a cross-sectional approach. The sample was obtained using the total sampling technique, namely all 34 nurses in the Emergency Room of Hospital X. The instruments used were workload questionnaires and work stress questionnaires. Data analysis was carried out univariately and bivariately with the Chi-Square correlation test. Result: The results of the statistical test obtained a value (p-value = 0.001), so it can be concluded that there is a significant relationship between workload and the level of work stress of nurses. Conclution: There is a relationship between workload and the level of work stress of emergency room nurses.